PENOLAKAN PERMOHONAN PERNYATAAN PAILIT PT RAMALDI PRAJA SENTOSA DI TINGKAT KASASI (STUDI KASUS: PUTUSAN MA NOMOR 196 K/PDT.SUS-PAILIT/2017) - Indira Rizty Raihanna; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2021)
A request for a bankruptcy statement can be filed by a debtor who has two or more creditors and does not pay off at least one overdue debt which can be billed and then declared bankrupt by a court decision. This study aims to determine whether the legal considerations of the Supreme Court judges in the Decision Number 196 K / Pdt.Sus-Pailit / 2017 who rejected the request for a bankruptcy statement by PT Ramaldi Praja Sentosa as the debtor were in accordance with the provisions of Law Number 37 of 2004 concerning Bankruptcy and Postponement. Debt Payment Obligations. This type of research used in this research is normative legal research. The legal considerations of the Supreme Court judges in Decision Number 196 K / Pdt.Sus-Pailit / 2017 were slightly wrong because the judge decided based on SEMA Number 2 of 2016 which requires creditor approval of the appointed curator as a formal requirement, where in law it only requires that an application for bankruptcy can be accepted if there are at least two creditors and one debt that has matured and can be collected. The additional requirement is proof of the debt, which must be simple. In this case the law does not require the approval of the creditors regarding the appointed curator. Therefore, the judge should have considered the requirements for bankruptcy petition that have been fulfilled in the Bankruptcy Law.